A robust, modular approach to produce graphene–MOx multilayer foams as electrodes for Li-ion batteries. Issue 12 (7th March 2019) - Xia, Zhen Yuan; Christian, Meganne; Arbizzani, Catia; Morandi, Vittorio; Gazzano, Massimo; Quintano, Vanesa; Kovtun, Alessandro; Palermo, Vincenzo
Abstract : Multilayer hierarchical electrodes for lithium batteries, made of vertically aligned nanowalls of hematite (Fe2 O3 ), alternated with horizontal spacers of reduced graphene oxide (RGO) on a 3D, conductive graphene foam. Abstract : Major breakthroughs in batteries would require the development of new composite electrode materials, with a precisely controlled nanoscale architecture. However, composites used for energy storage are typically a disordered bulk mixture of different materials, or simple coatings of one material onto another. We demonstrate here a new technique to create complex hierarchical electrodes made of multilayers of vertically aligned nanowalls of hematite (Fe2 O3 ) alternated with horizontal spacers of reduced graphene oxide (RGO), all deposited on a 3D, conductive graphene foam. The RGO nanosheets act as porous spacers, current collectors and protection against delamination of the hematite. The multilayer composite, formed by up to 7 different layers, can be used with no further processing as an anode in Li-ion batteries, with a specific capacity of up to 1175 μA h cm −2 and a capacity retention of 84% after 1000 cycles. Our coating strategy gives improved cyclability and rate capacity compared to conventional bulk materials. Our production method is ideally suited to assemble an arbitrary number of organic–inorganic materials in an arbitrary number of layers.